Analisi Efektivitas Pembelajaran Daring Spada Unisan Dengan Menggunakan Metode System Usability Scale - damopolii, muhlis; Lasulika, Mohamad Efendi; Mustofa, Yasil Aril (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
ABSTRACT ; Online learning is distance learning that is conducted indirectly or through face- to-face communication by video conferencing, uploading, and downloading materials and assignments via the internet. It is not new. It has been widely applied in high schools and universities but is ineffective due to the lack of facilities. It occurs in universities between students and lecturers. To make students and lecturers understand online learning, Universitas Ichsan Gorontalo, especially the Informatics Engineering Study Program, has carried out an online learning system using an application, commonly called SPADA UNISAN. It is provided to meet the needs of the teaching and learning process between students and lecturers to be more flexible, efficient, measurable, and enjoyable. The results of the analysis of online learning using the method of System Usability Scale) indicate that the results of the assessment given to 114 respondents obtain a score of 45%. with the Acceptability Ranges version obtains “Not Acceptable”. The grade scale results in terms of the level of user acceptance are included in the Poor Category, and the score obtained is above the average score. It means that this system cannot be accepted by its users and has been below the standard usability average value setKeywords: fuzzy Tsukamoto, online game addiction, duration, compulsion, Keywords: system analysis, online learning, SUS method